Analysis of Pharmacist Intervention in Anaemic Pregnant Women in Stunting Prevention - Amaliah, Riska; Nasution, Azizah; Khairunnisa (International Journal of Science, Technology & Management, 2023)
Accelerating stunting reduction is a national priority in realizing healthy, intelligent and productive human resources. Multi-dimensional factors cause stunting, so multi-sectors are responsible for handling it. To optimize stunting prevention, health workers such as pharmacists have an essential role to play. As part of change agents and competence, pharmacists should optimize their role in providing information and education and as caregivers. Pharmacists are expected to play a role in diet and nutrition management, increasing adherence to therapy, and monitoring drug side effects in pregnancy. This study aims to get an overview of the effect of pharmacist intervention in preventing anaemia in pregnant women in supporting the treatment of stunting. This type of research was a quasi-experimental study with a cohort study design before and after the intervention was carried out on anaemic pregnant women receiving blood supplement therapy in Pandeglang District, Banten Province. The clinical outcome assessment was measured based on the Hb value and the pregnant woman's weight. The level of adherence was assessed using the Medication Adherence Report Scale (MARS-5). The results showed increased adherence to using Iron Tablets after pharmacist intervention (99.47%). The MARS-5 score showed an average increase of 24.99 ± 0.07. The average patient's Hb increased after the intervention and showed a significant difference in Hb levels (p<0.05). The decrease in the number of patients with anaemia in pregnant women reached 91.8%. Pregnant women's weight increased monthly, showing a significant difference (p <0.05). Based on these results, it can be concluded that there was a significant increase in adherence to the consumption of Blood Supplement Tablets, Hb levels, and body weight in pregnant women after pharmacists intervened in Pandeglang Regency, Banten Province.